Pengaruh Pemberian Probiotik Berbeda pada Pakan Komersial terhadap Pertumbuhan Dan Efisiensi Pakan Ikan Lele Sangkuriang (Clarias Sp.) [ The Present Effect Of Different Probiotics On Commercial Feed Towards Growth And Feed Efficiency Of Sangkuriang Catfish (Clarias Sp.) ] - Muhammad Arief; Nur Fitriani; Sri Subekti (Faculty of Fisheries and Marine Universitas Airlangga, 2014)
Abstract Freshwater culture commodity such as sangkuriang catfish (Clarias sp.) has high sufficient demand. One way to fullfil necessity of sangkuriang catfis demand is accelerate the growth. The aim of this research is to determine the present effect of different probiotics on commercial feed towards growth and feed efficiency of sangkuriang catfish. The research using experimental method, using Completely Randomized Design (CRD). Sangkuriang catfish kept in 30 days with four treatments and five replications, that is P1 (control), P2 (5% probiotics A), P3 (5% probiotics B), and P4 (5% probiotics C). The obtained data were processed by Analysis of Variance (ANOVA) and followed by Duncan Multiple Range Test if there was significant data. The result showed that different probiotics giving significant effect to growth rate and feed efficiency (p<0,05). The best sangkuriang catfish (Clarias sp.) growth rate is P2 treatment 2,88% ± 0,38, and the lowest is P1 treatment at 1,73% ± 0,7. The best feed efficiency is P2 treatment at 54,69% ± 9,67 and the lowest is P1 treatment at 30,27% ± 12,65